Prevalence of hepatitis A virus in patients attending a referral hospital in Bubanza Province, Northwest Burundi - Harabandi, Rémy; Odari, Eddy O.; Lihana, Raphael W. (International Journal of Research in Medical Sciences, 2018)
Background: Viral hepatitis is a public health problem wide world. Hepatitis A, transmitted by fecal-oral route, is an infectious viral disease caused by hepatitis A virus and mainly due to poor sanitation. This study aimed to determine the prevalence of hepatitis A virus and associated factors in patients attending Mpanda referral hospital in Northwest Burundi. Methods: A cross-sectional study was done from November 2017 to January 2018 on 385 participants aged 2 years and above. Participants were recruited using a systematic random sampling technique. Data were collected using questionnaire from consented/assented participants. Five millilitres of venous blood was collected and analyzed. Anti-hepatitis A virus antibodies were screened using Enzyme Immuno Assay. Data were analyzed using Statistical Package for the Social Sciences version 16.0 software. A descriptive analysis was followed by bivariate analysis using a Chi-square test for comparison of various sub-groups with 5% statistical significance level. Odds ratio and 95% Confidence Intervals were calculated and presented. Results: The median age of the participants was 23 years and the range 72 years. The overall prevalence of Hepatitis A virus was 60.3%. There was a significant association between age [OR=7.22 (4.04-12.93), P <0.001], lack of clean water [OR=10.07 (5.63-18.01), P <0.001], traditional latrines [OR=1.86 (1.02-3.40), P=0.04] and Hepatitis A Virus seroprevalence. Conclusions: Present study shows high prevalence of HAV infection in patients attending Mpanda Referral Hospital. Younger age, lack of clean water and traditional latrines play roles in increasing prevalence of HAV infection in both rural and urban areas.